Adams-Stokes attack as the first symptom of acute rheumatic fever: report of an adolescent case and review of the literature - Carano Nicola; Bo Ilaria; Tchana Bertrand; Vecchione Erica; Fantoni Silvia; Agnetti Aldo (BMC, 2012)
Abstract Background Acquired complete heart block, in pediatric age is mainly the results of direct injury to conduction tissue during cardiac surgery or cardiac catheterisation. It can also be observed in different clinical settings as infectious diseases, neoplasia, and inflammatory diseases. It has a wide range of presentation and in some settings it can appear a dramatic event. Although a rare finding during acute rheumatic fever, with a transient course, it may need a specific and intensive treatment. Case presentation We report the case of an Adams-Stokes attack in an adolescent with acute rheumatic carditis and complete atrio-ventricular block. The attack was the first symptom of carditis. We reviewed the literature and could find 25 cases of complete atrio-ventricular block due to rheumatic fever. Ten of the 25 patients experienced an Adams-Stokes attack. Nineteen of the 25 patients were certainly in the pediatric age group. Seven of the 19 pediatric cases experienced an Adams-Stokes attack. In 16/25 cases, the duration of the atrio-ventricular block was reported: it lasted from a few minutes to ten days. Pacemaker implantation was necessary in 7 cases. Conclusion Rheumatic fever must be kept in mind in the diagnostic work-up of patients with acquired complete atrio-ventricular block, particularly when it occurs in pediatric patients. The insertion of a temporary pacemaker should be considered when complete atrio-ventricular block determines Adams-Stokes attacks. Complete heart block during acute rheumatic fever is rare and is usually transient. Along with endocarditis, myocarditis and pericarditis, complete atrio-ventricular block has been recognized, rarely, during the course of acute rheumatic carditis.